Carbon dot nano convex carbon wire and preparation method thereof
By oxidizing and nitriding the silicon substrate, the concentrated acrylonitrile fibers were deposited using electrical-fluid mechanical jets and thermally stabilized and carbonized to form carbon dot nano-protruding carbon lines, which solved the carbon dot growth on the surface of the carbon line. The problem of difficult to highlight optical properties has achieved improvement in the optical properties of carbon lines and simplification of the preparation process.
Patent Information
- Application Number
- CN202411265875.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-10
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-09-10
AI Technical Summary
When the carbon dots are grown on the surface of the carbon wire, it is difficult to distinguish between the size of graphite particles and the relative proportion of the oxidation surface defects, resulting in difficult to highlight the optical properties of the carbon wire, and the growth method is complex, making it difficult to control the number and dispersion of the carbon dots.
By oxidizing and nitriding the silicon substrate, the polyacrylonitrile fibers are deposited using electrical-fluid mechanical jets, thermal stabilization and carbonization are carried out to form carbon dot nano-protrusion carbon lines, and the number and degree of dispersion of carbon dots are controlled.
It significantly improves the optical properties of the carbon line, enhances the G-peak and D+G-peak intensities of the photoelectron spectroscopy and Raman spectroscopy, simplifies the preparation process, and is suitable for large-scale production.
Smart Images

Figure HDA0005037117680000011 
Figure HDA0005037117680000021 
Figure HDA0005037117680000022
Abstract
Description
Technical Field
[0001] The invention relates to a carbon nanodot, in particular to a carbon dot nano-protrusion carbon wire formed by in-situ growth of carbon nanodots on the surface of a nano-carbon wire, and also to a preparation method thereof, belonging to the technical field of carbon nanomaterials. Background Art
[0002] Nanostructuring the surface of carbon wires through carbon spheres, conformal TiO2, photonic crystal structures, photonic architectures, and hollow core photonic crystal microjunctions can make the optical properties of carbon wires excellent. Typically, carbon dots (CDs) are dispersed in solution and not present on the surface of carbon wires (for example, literature: Carbon 173, 433-447 (2021); J. Appl. Phys. 127, 231101 (2020); ACS Sens. 8, 3812-3823 (2023); Nature Communications, 12: 812 (2021); Carbon 186, 91-127 (2022); ACS Nano 14, 6127-6137 (2020) etc.), which exhibit better optical properties in applications such as anti-cancer therapy, photocatalysis, bioimaging, and optical sensing. Growing carbon dots on the surface of carbon wires is expected to open up unique new photonic mechanisms and devices.
[0003] Current CDs growth methods include microwave-assisted pyrolysis, chemical oxidation, hydrothermal / solvothermal reaction, and laser ablation. The prepared carbon dots have conjugated sp 2 The core and surface of the structure are rich in nitrogen and oxide chemical groups, which are closely related to the photophysical properties. Raman spectroscopy can reflect the sp 2 structure. In the Raman spectrum of CDs, the -1 and 1590cm -1 The D and G peaks reflect the sp 3 and sp 2 Graphitic properties of carbon. The high dependence of the emission wavelength on the energy migration from the initial graphite nucleus to the surface defects is explained, which stimulates the extended spectrum of CDs. The relative contribution of graphite particle size and oxidized surface defects to the optical properties of CDs is difficult to distinguish due to the formation of indistinguishable impurity products prepared by hydrothermal and solvothermal syntheses. It becomes extremely difficult to highlight the optical properties of carbon lines by extending the CD spectrum because both graphite particle size and oxidized surface defects contribute to the CDs. Summary of the invention
[0004] In view of the defects of the prior art, the first object of the present invention is to provide a carbon dot nano-protrusion carbon wire, which can significantly improve the optical properties of the carbon wire by forming carbon dots on the surface of the carbon wire and has a wider application prospect.
[0005] The second object of the present invention is to provide a method for preparing carbon dot nano-protrusion carbon wires, which comprises pre-treating a silicon substrate by oxidation and nitridation, using electro-fluid dynamics jetting to deposit nano-protrusion PAN wires on the pre-treated silicon substrate, and then performing thermal stabilization and carbonization to obtain carbon dot nano-protrusion carbon wires. This method can not only form carbon dots on nano-protrusion carbon wires, but also control the number and dispersion of carbon dots.
[0006] In order to achieve the above technical objectives, the present invention provides a method for preparing carbon dot nano-raised carbon wires, which method comprises pre-treating a silicon substrate by oxidation and nitridation, depositing polyacrylonitrile fibers on the surface of the pre-treated silicon substrate by electro-hydraulic jetting, and then sequentially performing thermal stabilization treatment and carbonization treatment to obtain carbon dot nano-raised carbon wires.
[0007] In order to achieve the above technical objectives, the present invention provides a method for preparing carbon dot nano-raised carbon wires, which method comprises pre-treating a silicon substrate by oxidation and nitridation, depositing polyacrylonitrile fibers on the surface of the pre-treated silicon substrate by electro-hydraulic jetting, and then sequentially performing thermal stabilization treatment and carbonization treatment to obtain carbon dot nano-raised carbon wires.
[0008] The key points of the preparation method of carbon dot nano-protrusion carbon wire provided by the present invention are: on the one hand, by oxidizing and nitriding the silicon substrate, a nitrogen-doped silicon dioxide layer is generated on the silicon substrate, and the substrate can induce the carbonization process of polyacrylonitrile fibers and transform them into carbon nanowires grown in situ on the surface; on the other hand, depositing polyacrylonitrile fibers by spraying is conducive to controlling the morphology of polyacrylonitrile fibers, such as obtaining polyacrylonitrile fibers with a semicircular cross-section, which is a key factor in achieving the growth of carbon dots on the surface of carbon wires; at the same time, the size of PAN fibers can be easily controlled by spraying, and the pore size of the porous microstructure contained in the polyacrylonitrile fibers can be reduced to 0 by controlling the diameter of the polyacrylonitrile fibers, thereby transforming them into hidden nodes. These hidden point microstructures can be transformed into carbon dots grown in situ on the carbon wires after thermal stabilization and carbonization treatment.
[0009] As a preferred solution, the oxidation pretreatment conditions are: air atmosphere, oxidation at 900-1000°C for 3-5h. The purpose of the oxidation treatment is to generate a layer of silicon dioxide in situ on the silicon substrate. By controlling the appropriate temperature and time, the thickness of the silicon dioxide layer can be controlled to be about 1 micron.
[0010] As a preferred solution, the nitridation pretreatment conditions are: nitridation at 950-1050°C for 1-4 hours in a nitrogen atmosphere. After proper nitridation treatment, a proper amount of nitrogen can be doped into the silicon dioxide layer, and the doping of nitrogen atoms can change the surface properties of the silicon dioxide layer, which has a significant effect on the morphology of the deposited polyacrylonitrile fiber and the carbonization process.
[0011] As a preferred solution, the process of depositing polyacrylonitrile fiber is as follows: PAN solution is used as the spray liquid, the temperature of the PAN solution is 106-115°C, the treated silicon substrate is used as the receiving substrate, the distance between the spray needle and the receiving substrate is 1.8-1.95mm, the spray voltage is 500V-800V, the moving speed of the spray needle is 500-2400m / s, and the moving speed of the receiving substrate is 0.6-10m / s. Under the action of high voltage, the DMF solution droplet of PAN at the needle tip can be driven to transform into a continuous PAN-based jet, and the solvent evaporates during the movement of the PAN-based jet toward the receiving substrate, so that the PAN-based jet is transformed into PAN fiber. By controlling the movement of the receiving substrate, the PAN fiber deposited on the surface of the silicon substrate is patterned. The spray voltage is an important factor affecting the morphology and size of the polyacrylonitrile fiber. The closer the spray voltage is to 800V, the closer the cross-section of the polyacrylonitrile fiber is to a semicircular shape, and its diameter is more conducive to the generation of carbon lines of surface-grown carbon dots. The spray voltage is preferably 600 to 800V, more preferably 700 to 800V.
[0012] As a preferred solution, the mass concentration of the PAN solution is 8-9%; the PAN solution is a PAN / DMF solution. If the concentration of the PAN solution is too high or too low, it is difficult to meet the electro-hydraulic injection requirements for the preparation of carbon dot nano-protrusion carbon wires.
[0013] As a preferred solution, the heat stabilization treatment condition is: in an air atmosphere, at a temperature of 110-115° C., and heat preservation for 8-13 hours. The heat stabilization process can completely volatilize the excess solvent in the polypropylene fiber and stabilize the molding.
[0014] As a preferred solution, the carbonization treatment conditions are: in a protective atmosphere, the temperature is raised to 1000-1050°C at a heating rate of 10-20°C / min and kept at this temperature for 1.0-1.5 hours. 2、 CO, HCN, H2O, O 2、 NH 3、 Small molecules such as CH4 are carbonized and graphitized. The heating rate mainly affects the removal rate of small molecules in polyacrylonitrile, thereby affecting the morphology of carbon wire materials.
[0015] The PAN / DMF solution of the present invention is formed by dissolving polyacrylonitrile (PAN) particles into N,N-dimethylformamide (DMF) under heating and magnetic stirring.
[0016] When the PAN / DMF solution of the present invention is heated to 106° C., its shear, loss modulus and conductivity properties become excellent, and these outstanding properties ensure electro-fluid dynamics injection under high local electric field.
[0017] The present invention also provides a carbon dot nano-protrusion carbon line, which is obtained by the preparation method.
[0018] Compared with the prior art, the technical solution of the present invention has the following beneficial technical effects:
[0019] The carbon dot nano-protrusion carbon wire of the present invention can significantly improve the optical properties of the carbon wire by in-situ forming carbon dots on the surface of the carbon wire. For example, forming carbon dots on the continuous carbon wire can enhance the G peak and D+G peak intensity of the photoelectron spectrum and Raman spectrum.
[0020] The method for preparing carbon dot nano-protruding carbon wires of the present invention comprises pre-treating a silicon substrate by oxidation and nitridation, depositing nano-protruding PAN wires on the pre-treated silicon substrate using electro-fluid dynamics jetting, and then stabilizing and carbonizing, thereby forming carbon dots on the nano-protruding carbon wires and controlling the number and dispersion of the carbon dots.
[0021] The preparation method of the carbon dot nano-protrusion carbon wire of the present invention is simple, low-cost and conducive to large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 Figure 2 is the synthesis process of carbon wire with carbon dot nano-protrusions: a is the manufacturing process of carbon wire with carbon dot surface; b is the scanning electron microscope image and profile of trapezoidal PAN fiber, d is the scanning electron microscope image and profile of semicircular PAN fiber, c is the image and profile of carbon wire without carbon dots, and e is the image and profile of carbon wire with carbon dots. Figure 2 Figure 3 Control of carbon dots based on PAN microstructure: a is the manufacturing process of PAN fiber to carbon dots; b and e are the scanning electron microscope image and contour image of PAN fiber; c and f are the scanning electron microscope image and contour image of carbon wire; among them, b and c are porous microstructures; e and f are carbon dot microstructures, d is the correlation between the pore structure and diameter of carbon wire, and d is the functional relationship between the ratio of carbon dot size to diameter and the diameter of carbon wire. Figure 3Figure 3 shows the effect of carbon wire diameter and oxidation reaction on the nanostructuring of carbon dots in the absence of nitrogen pretreatment; a is the transition from PAN conformation to carbon dots; b is the scanning electron microscope image and contour image of PAN fiber with hidden node microstructure of PAN; c, d, e are atomic force microscope images and contour images of nanoconvex carbon wires with diameters of 191nm, 177nm, and 268nm, respectively; f is the scanning electron microscope image, atomic force microscope image and contour image of broken carbon wires after oxidation treatment; g is the X-ray photoelectron energy spectrum of the carbon wire in figure f; h is the dependence of the axial carbon dot spacing on the carbon wire diameter and carbon dot density.
[0023] Figure 4 Effect of carbon wire contact surface on the nanostructuring of carbon dots; a is the evolution of carbon dots on different substrates; b is silica surface; c is silicon surface; d is nitrogen surface (nitrided silica surface); e is carbon wire suspended between carbon supports; F is the shrinkage rate of PAN fiber to carbon wire on different contact surfaces, and g is the correlation between the number of carbon dots per unit area and the shrinkage rate.
[0024] Figure 5 Characterization of carbon dots on carbon wires; a is a carbon wire on a carbon surface, b is a broken carbon wire on a silicon dioxide surface; c is a scanning electron microscope and atomic force microscope of a carbon dot-based carbon wire. d~f are X-ray photoelectron spectra of carbon wires in a, b and c respectively; g~i are Raman spectra of carbon wires in a, b and c respectively. DETAILED DESCRIPTION
[0025] The following specific examples are intended to further illustrate the present invention, rather than to limit the scope of protection of the claims of the present invention.
[0026] Example 1
[0027] 1. Place the silicon wafer in an oxidation furnace and perform oxidation treatment at 1000°C for 4 hours in an air atmosphere to form a 1000nm oxide layer on the surface of the silicon wafer;
[0028] 2. Place the oxidized silicon wafer in a pyrolysis furnace under nitrogen environment and carry out nitridation treatment at 1000℃ for 1 hour to form Figure 1 A silicon substrate having a silicon dioxide layer and a nitrogen layer as shown;
[0029] 3. Polyacrylonitrile (0.27 g) and dimethylformamide (3 g) were mixed, heated (heating temperature was 106° C.) and stirred to prepare a polyacrylonitrile solution;
[0030] Fourth, using polyacrylonitrile solution and its electro-hydraulic fluid jetting process (jetting voltage 800V, the distance between the spray needle and the silicon wafer surface is 1.95mm, the moving speed of the spray needle is 2400m / s, and the substrate on which the silicon wafer is located moves at a speed of 0.6m / s), polyacrylonitrile fibers are deposited on the surface of the silicon wafer pretreated with oxidation and nitrogen to form Figure 1 The polyacrylonitrile fiber pattern shown; wherein, in the electrohydraulic fluid jetting process of the polyacrylonitrile solution: 1) first apply a voltage of 500V between the silicon wafer and the spray needle; 2) control the flow rate of the polyacrylonitrile solution in the spray needle to be 0-1nL / min by the injection pump; 3) reduce the distance between the spray needle and the silicon wafer until the polyacrylonitrile droplet on the spray needle contacts the substrate where the silicon wafer is located, deforms and returns to 1.95mm, thereby activating the electrohydraulic fluid jetting to form the polyacrylonitrile jet fiber; 4) increase the voltage between the silicon wafer and the spray needle to 800V by controlling the power supply; 5) further move the spray needle at a speed of 2400m / s and move the substrate where the silicon wafer is located at a speed of 0.6m / s to ensure that continuous polyacrylonitrile fibers are deposited on the surface of the silicon wafer treated with oxidation and nitrogen;
[0031] 5. The polyacrylonitrile fiber and its silicon wafer were subjected to a thermal stabilization treatment at 115°C (air environment, constant temperature of 115°C, heating time of 13 hours) and a carbonization treatment at 1000°C (heating rate from 115°C to 1000°C was 14.5°C / min). The carbonization treatment time was 1 hour. The polyacrylonitrile fiber was converted into nanoconvex carbon wires and carbon points were formed on the nanoconvex carbon wires.
[0032] from Figure 1 As can be seen in the figure, at a 500V jetting voltage, the cross-section of the PAN fiber received by the silicon substrate is a trapezoid. As the jetting voltage changes to 800V, the cross-section of the PAN fiber changes from a trapezoid to a semicircle. When the jetting voltage reaches above 600V, up to 800V, the cross-section of the PAN fiber received by the silicon substrate treated with oxidation and nitridation is a semicircle (see Figure 1 (a). The PAN fibers received by the silicon substrate were treated with air thermal stabilization and carbonized in a nitrogen atmosphere at 1000°C. The PAN fibers with a trapezoidal cross section were transformed into a graphite-like carbon structure, but no carbon dots were grown on the carbon wires (see Figure 1 b and c). As the injection voltage decreases to 800 V, the diameter of the PAN fiber decreases from 3.05 μm to 0.81 μm, and the cross-section of the corresponding PAN fiber can be transformed from a trapezoidal shape to a semicircular shape. This cross-section transformation is the key factor for the growth of carbon dots onto the surface of the carbon wire. The PAN fiber received by the silicon substrate pretreated by oxidation and nitridation is transformed into a nanoconvex carbon wire and the carbon dots grow on the surface of the nanoconvex carbon wire.
[0033] Figure 2The carbon dot nanostructuring based on PAN fiber microstructure is demonstrated. Using electrohydraulic fluid jetting, PAN / DMF solution is transformed into PAN fibers, and the molecular chains in PAN fibers are assembled into a porous microstructure in the form of a helical conformation ( Figure 2 (a). By reducing the injection voltage, the PAN fiber diameter corresponding to the voltage is reduced, and the pore size of the porous microstructure in the PAN fiber is reduced to 0. This ensures that the PAN hidden node grows on the semicircular PAN fiber, but it cannot be effectively highlighted on the semicircular cross section (see Figure 2 (a). After heat stabilization and carbonization pretreatment of PAN fibers, these PAN hidden nodes are transformed into carbon dots, which are clearly prominent on the semicircular cross section (see Figure 2 (a). When the transition from porous microstructure to PAN hidden point microstructure is absent, the porous microstructure is reflected from PAN fibers to carbon wires after thermal stabilization and carbonization (see Figure 2 However, during the thermal stabilization and carbonization pretreatment, cyclization, dehydrogenation, denitrification and decyanation reactions occur, and the gases H2, CO, HCN, H2O, O2, NH3, CH4, etc. produced by these reactions are released. The gas release occurs on the porous microstructure, and the pore size of the porous microstructure increases from 15nm to 78nm (see Figure 2 By reducing the diameter of the carbon wire to 620 nm, the ratio of the pore size to the carbon wire diameter is reduced from 4.047% to 0 (see Figure 2 When PAN hidden points appear on the surface of PAN fibers, carbon dots can grow on the corresponding carbon lines (see Figure 2 b, e and f). When the carbon wire diameter decreases from 620nm to 100nm, the carbon dot size on the carbon wire increases from 24nm to 100nm. This reveals a trend that the ratio of carbon dot size to carbon wire diameter increases to 100%. This trend indicates that the growth of carbon dots on carbon wires requires controlling the diameter of the carbon wire between 100nm and 620nm in order to avoid the ratio of carbon dot size to carbon wire diameter reaching 100%. Furthermore, the relationship between carbon dots and PAN microstructure reveals that the growth of carbon dots depends on PAN-based hidden nodes rather than porous microstructures.
[0034] Comparative Example 1
[0035] Compared with Example 1, the difference is that after the silicon substrate is oxidized, no nitridation is performed. The PAN hidden nodes are transformed into carbon nodes, and the density of these carbon nodes is relatively small (see Figure 3 a). Controlling the carbon wire diameter and using oxidation treatment (see Figure 3 a, c~g), the density of carbon dots increases and the distance between carbon dots decreases to near 0 (see Figure 3f). The corresponding carbon wires are broken into carbon dots, which ensures the formation of carbon dots in the broken carbon wires. The above carbon dot nanostructuring based on the carbon wire diameter and oxidation treatment can increase the carbon dot density on the carbon wire surface to a high level.
[0036] During the nanostructuring of carbon dots, the nitridation pretreatment step was removed and the diameter of the PAN fibers was reduced to ~100 nm, and the PAN hidden nodes became extremely inconspicuous. However, after the carbonization treatment of the PAN hidden nodes, a large number of carbon dots were formed. The XPS O1s spectra of these carbon-based dots showed 46.14% and 53.86% intensities of oxygen, respectively. Among them, 46.14% of the intensity of oxygen came from silica; 53.86% of the intensity of oxygen came from groups such as acridone-type carbonyl, carbonyl and alcohol groups. These confirmed the oxidation of the carbon dots. The carbon lines composed of these oxidized carbon dots showed complete fragmentation and did not present a flat semicircular cross-sectional shape (see Figure 1 Zhongehe Figure 3 f). This indicates that the oxidation reaction on the silicon substrate in the absence of nitrogen pretreatment can break up the carbon wires into carbon dots.
[0037] When the oxidation reaction is carried out, the carbon wire diameter increases from 191nm to 270nm, the carbon wire breaks into carbon dots, the corresponding carbon dots can be aggregated together, and their number increases to a greater extent. In the absence of oxidation reaction, the carbon wire diameter decreases from 191nm to 177nm, and the carbon wire diameter increases from 177nm to 268nm, and the number of carbon dots can increase from 4 to 8 to 32 (see Figure 3 c~e). The axial distance between the corresponding carbon dots shows a trend of periodically decreasing to 0. Among them, the diameter of the carbon wire is controlled between 480nm and 100nm. This shows that the regulation of the carbon wire diameter can increase the density of carbon dots. In the area where the carbon dot spacing approaches 0, the carbon dot density can be increased from a relatively low level to a relatively high level by controlling the carbon wire diameter between 315nm and 325nm; these indicate that changing the carbon wire diameter using the spray voltage can nanostructure these carbon dots.
[0038] Comparative Example 2
[0039] Compared with Example 1, the difference is that the carbon wires are prepared on different substrates (see Figure 4 b~e). Among them, the carbon wire on the silicon dioxide surface is broken into a large number of carbon dots, which gather together and closely contact the silicon dioxide surface. When the contact surface is replaced with a nitrided silicon dioxide surface, the carbon dots can grow on the carbon wire surface instead of on the silicon dioxide surface (see Figure 4 When the contact surface is replaced by carbon and air, no carbon dots grow on the surface of the carbon wire (see Figure 4 a, 4d and 4e). This indicates that the growth of C-dots depends on the contact surface of C-wires, such as SiO2 and N2.
[0040] The material that the PAN fiber contacts during the thermal stabilization and carbonization process of the PAN fiber to carbon wire is a major factor affecting the nanostructuring of the carbon dots on the carbon wire. By changing the contact material, the diameter of the carbon fiber decreases from 465nm to 244nm, then to 25nm, and finally to 12nm. Figure 4 In f, the shrinkage rate of the corresponding PAN fiber to the carbon line increases from 9% (the contact material is silicon dioxide) to 12.5% (the contact material is silicon nitride), then to 80% (the contact material is carbon), and finally to 93% (the contact material is air). Figure 4 g, the greater the shrinkage, the fewer the number of carbon dots per unit area. When the size of carbon dots decreases from nanoscale to 0, the number of carbon dots per unit area decreases to 0.
[0041] Using the above fabrication method, carbon wires were grown on carbon surfaces (see Figure 5 a), silicon dioxide surface without nitrogen pretreatment (see Figure 5 b) and nitridation pre-treated silicon dioxide surfaces (see Figure 5 These carbon lines show carbon-free points (see Figure 5 a), broken carbon points (see Figure 5 b) and continuous carbon dots (see Figure 5 c). Carbon lines without carbon dots (see Figure 5 a) The N1s XPS spectrum shows a signal A with an intensity of 28.46% and a signal B with an intensity of 71.54% (see Figure 5 d). Among them, signal A responds to the nitrogen on the naphthyridine ring and the hydrogen naphthyridine ring; signal B responds to the nitrogen in the propylene ketone ring bond. When the carbon wire changes from no carbon dots to broken carbon dots, the intensity of signal A increases from 28.46% to 65.66%, and the intensity of signal B decreases from 71.54% to 34.34%. This shows that broken carbon dots can increase the intensity of signal A before. When broken carbon dots are transformed into aggregated carbon dots on the surface of carbon wires, the intensity of signal A increases from 65.66% to 80.11%. Obviously, growing continuous carbon dots on the surface of carbon wires can show the advantage of enhancing signal A.
[0042] The carbon lines without carbon dots appear at 1350 cm in the Raman spectrum. -1 D peak signal, 1590cm -1 The G peak signal, 2700cm -1 2D peak signal, 2950cm -1 D+G peak signal, 3180cm -1 The 2G peak signal (see Figure 5 g). Thus, the intensity ratio of the D peak to the G peak (I D / IG ) is 0.996; the intensity ratio of D peak to D+G peak (I D / I D+G ) is 3.01. When the carbon wire is broken into a large number of carbon dots, I D / I G From 0.996 to 1.411, I D / I D+G Increased from 3.01 to 5.45 ( Figure 5 I D / I G and I D / I D+G The increase in I indicates that the broken carbon dots exhibit a higher D peak intensity. When the broken carbon dots connect together and grow to the surface of the carbon wire, I D / I G From 0.996 or 1.411 to 0.768, I D / I D+G From 3.01 or 5.45 to 2.66 (see Figure 5 gi). D / I G and I D / I D+G The decrease in indicates that the continuous carbon dots have stronger D peak and D+G peak signals.
Claims
1. A method for preparing carbon dot nano-protrusion carbon wires, characterized in that: The silicon substrate is pre-treated by oxidation and nitridation, polyacrylonitrile fibers are deposited on the surface of the pre-treated silicon substrate by electro-hydraulic jetting, and then thermal stabilization treatment and carbonization treatment are performed in sequence to obtain carbon dot nano-protrusion carbon lines.
2. The method for preparing carbon dot nano-protrusion carbon wire according to claim 1, characterized in that: The oxidation pretreatment conditions are: air atmosphere, oxidation at 900-1000° C. for 3-5 hours.
3. The method for preparing carbon dot nano-protrusion carbon wire according to claim 1, characterized in that: The conditions of the nitridation pretreatment are: nitridation at a temperature of 950-1050° C. for 1-4 hours in a nitrogen atmosphere.
4. The method for preparing a carbon dot nano-protrusion carbon line according to any one of claims 1 to 3, characterized in that: The process of depositing polyacrylonitrile fiber is as follows: PAN solution is used as the spray liquid, the temperature of the PAN solution is 106-115° C., the treated silicon substrate is used as the receiving substrate, the distance between the spray needle and the receiving substrate is 1.8-1.95 mm, the spray voltage is 500V-800V, the moving speed of the spray needle is 500-2400m / s, and the moving speed of the receiving substrate is 0.6-10m / s.
5. The method for preparing carbon dot nano-protrusion carbon wire according to claim 4, characterized in that: The mass concentration of the PAN solution is 8-9%; the PAN solution is a PAN / DMF solution.
6. The method for preparing carbon dot nano-protrusion carbon wire according to claim 1, characterized in that: The heat stabilization treatment is carried out under the following conditions: in an air atmosphere, at a temperature of 110 to 115° C., and for 8 to 13 hours.
7. The method for preparing carbon dot nano-protrusion carbon wire according to claim 1, characterized in that: The carbonization treatment conditions are: in a protective atmosphere, heating to 1000-1050° C. at a heating rate of 10-20° C. / min, and keeping the temperature for 1.0-1.5 hours.
8. A carbon dot nano-protrusion carbon wire, characterized in that: The method is obtained by any one of claims 1 to 7.
Citation Information
Patent Citations
Preparation method of mace-shaped SiOC / C two-stage interface coating on carbon fiber surface
CN117661316A
Near-molecular-scale graphene nanofiber and preparation method thereof
CN118422381A
Electron emission source and its manufacturing method
JP2004288460A
Fabrication of ultra-fine metal oxide decorated hybrid carbon nanofibers by single-nozzle co-electrospinning method using a phase-separated mixed polymer solution
KR1020130075487A
Cited By
Superstrong radial graphitized carbon nanowire and preparation method thereof
CN119954151A
